Participatory Learning for Rural Community Empowerment - Sucipto, Sucipto; Fatihin, Muhammad (Universitas Negeri Malang, 2024)
Non-formal education is crucial in delivering education programs based on local wisdom. Community Learning Centers (CLCs) help combat illiteracy in Indonesia with flexibility, equality, and independence principles. Before implementing the independent learning policy, non-formal education institutions had already organized programs to liberate people from limitations. The Dial Foundation assists local communities in improving their quality of life through the Sustainable Livelihood Approach (SLA), categorizing non-formal learning programs into three types: informational, institutional, and developmental. Community involvement in asset identification and valuation is beneficial for understanding the actual conditions of their area, which are then categorized into five capitals: human capital, natural capital, financial capital, physical capital, and social capital. This allows the community to develop short-, medium-, and long-term sustainable development strategy plans. Community learning resources come from natural resources, traditions, culture, and external sources. The learning practices implemented by the Dial Foundation support sustainable development goals, particularly in providing quality education, enhancing health literacy, protecting mountainous regions, promoting effective housing governance, ensuring local food security, improving the quality of micro-scale business production, and advancing sustainable agriculture